Pengaruh Model Pembelajaran Creative Problem-Solving (CPS) Terhadap Pemahaman Konsep IPA Siswa Kelas IV SDN Purwodadi 01 - Iis Lestari; Nur Laili; Ria Kurniawati; Shirly Rizki Kusumaningrum (Departement of Mathematics Education, 2021)
The purpose of this research is to know the influence of learning using a creative problem-solving model which was implemented in SDN Purwodadi 01. The sample quantity of 57 students consisted of an experimental class and a control class. The research design uses quasi experimental design with nonequivalent control group design. The results of the research show that there is influence of creative problem-solving models to understand the concept of science proved on different mean results after being treated. The experimental class has an average posttest score of 77 higher than the control class with an average posttest score of 64. The t-test result (independent sample t-test) which shows the significance of 0.00<0.05, then it can be concluded that Ho is rejected, and Ha is accepted, means creative problem-solving model has effect on understanding science concepts of grade 4 students of SDN Purwodadi 01.